2019
DOI: 10.1111/os.12474
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Finite Element Analysis of a Three‐dimensional Dynamic Model of Upper Cervical Spine Instability

Abstract: Objectives To establish a dynamic three‐dimensional (3D) model of upper cervical spine instability and to analyze its biomechanical characteristics. Methods A 3D geometrical model was established after CT scanning of the upper cervical spine specimen. The ligament of the specimen was fatigued to establish the upper cervical spine‐instability model. A 100‐N preloaded stress was applied to the upper surface of the occipital bone, and then a 1.5‐Nm moment was applied in the occipital‐sagittal direction to simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…A recent in vivo study showed that the exion-extension of C1-2 was 13.7 ± 4.2°, accounting for 14.5% of the overall exion-extension ROM; the lateral bending neck motion of C1-2 was 7.6 ± 2.7°, accounting for 13.2% of the overall lateral bending ROM; and the axial torsion neck motion of C1-2 was 72.9 ± 7.6°, accounting for 73.2% of the overall rotation ROM [22]. Previous investigations also achieved similar results [23,24,25]. Once the motion of C1-2 joint is restricted by the anterior continuous bony bridge, the bearing force capacity from the skull and the neck is in turn reduced, which further increases the risk of cervical fracture.…”
Section: Declarationssupporting
confidence: 56%
“…A recent in vivo study showed that the exion-extension of C1-2 was 13.7 ± 4.2°, accounting for 14.5% of the overall exion-extension ROM; the lateral bending neck motion of C1-2 was 7.6 ± 2.7°, accounting for 13.2% of the overall lateral bending ROM; and the axial torsion neck motion of C1-2 was 72.9 ± 7.6°, accounting for 73.2% of the overall rotation ROM [22]. Previous investigations also achieved similar results [23,24,25]. Once the motion of C1-2 joint is restricted by the anterior continuous bony bridge, the bearing force capacity from the skull and the neck is in turn reduced, which further increases the risk of cervical fracture.…”
Section: Declarationssupporting
confidence: 56%
“…It can provide information about stress distribution, deformation, and strain on any part of the cervical vertebrae during simulated manipulations, containing flexion, extension, and torsion [ 8 ]. Recently, different finite element models (FEM) of the cervical spine were constructed to investigate the biomechanics of the cervical spine or intervertebral disc [ 9 11 ]. However, few studies have established a FEM based on CSR, and few studies have performed biomechanical analysis of stress distribution, deformation of the model when imitating manipulation therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental biomechanics and theoretical biomechanics are two of the most common spinal biomechanics research methods. Compared with experimental biomechanics, theoretical biomechanics has its unique advantages: it can not only avoid high experimental costs and limited material sources, but also realize the prediction of the internal stressstrain eld of the spine [25][26]. As a theoretical biomechanical research method, FE analysis has been used for many years in the research of spinal mechanics [27][28].…”
Section: Discussionmentioning
confidence: 99%